2003
DOI: 10.1007/s00436-003-1006-3
|View full text |Cite
|
Sign up to set email alerts
|

Protective immunity against Toxoplasma gondii in mice induced by the SAG2 internal image of anti-idiotype antibody

Abstract: A monoclonal antibody TGCM5 (isotype G, subclass 1, kappa light chain) against SAG2, a major surface antigen of Toxoplasma gondii tachyzoites, was produced in quantity and its Fab-containing idiotype (Id) was injected into rabbits for production of rabbit anti-Id sera. The rabbit anti-Id IgG (aId-IgG) with a SAG2 internal image was obtained by purification with a protein A column. Significant lymphocyte proliferation induced by tachyzoite lysate antigen was observed in BALB/c mice that received two injections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 22 publications
0
21
1
Order By: Relevance
“…2b). The molecular mass of the recombinant SAG1/2 protein is slightly larger than the one expressed using E. coli (52 kDa; Yang et al 2003). The discrepancy in size between the recombinant and native (SAG1, 30 kDa and SAG2, 22 kDa) may be attributed to posttranslational modification involving glycosylation of the polypeptide backbone.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…2b). The molecular mass of the recombinant SAG1/2 protein is slightly larger than the one expressed using E. coli (52 kDa; Yang et al 2003). The discrepancy in size between the recombinant and native (SAG1, 30 kDa and SAG2, 22 kDa) may be attributed to posttranslational modification involving glycosylation of the polypeptide backbone.…”
Section: Discussionmentioning
confidence: 97%
“…This IL-12 then activates natural killer cells and T cells to also produce interferon-γ (IFN-γ), which, along with TNF-α, produce a synergistic response and inhibit the intracellular replication of tachyzoites (Sher et al 1993). The IFN-γ response is mainly brought about by CD8+ T cells and CD4+ T cells, the former being the more proactive of the two (Thomas 2001;Yang et al 2003). In order to maintain immunity, IFN-γ has to be secreted continuously for as long as possible (Subauste and Remington 1993).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that induction of both lymphocyte proliferation and IFN-γ production (one of Th1-type cytokines) positively correlates with protective Th1 cell-mediated immunity against T. gondii [43,44,51]. In addition, IFN-γ has been demonstrated to be a critical mediator that has to be secreted for as long as possible in order to maintain anti Toxoplasma immunity [52,53].…”
Section: Protective Immunity By Toxoplasma Sag-loaded Microparticlesmentioning
confidence: 99%